(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 1998)
In this paper, an analysis of the noun phrases of the south Mapuche dialect, chesungun, is presented. The noun and adjective functions are reviewed and pluralizer particles and some structures which are used to express adjective gradation are shown.